Research for Practice: Convergence. - KLEPPMANN, MARK (Communications of the ACM, 2022)
The article presents a selection of research papers focusing on the theme of convergence, also known as eventual consistency, and specific computer science topics including systems, programming languages, human-computer interaction, and data management. Topics include conflict-free replicated data type (CRDT), consistency as logical monotonicity (CALM), and mergeable replicated data types (MRDTs).